1967
DOI: 10.1104/pp.42.12.1665
|View full text |Cite
|
Sign up to set email alerts
|

Low Energy Effects of Light on Growth and Pigment Content in a Yellow-in-the-Dark Mutant of Chlamydomonas reinhardi

Abstract: Summary. The y-2 mutant of Chlamydomitonas reinhardi differs from the wild type in being uinable to synthesize chlorophyll in the dark and in a reqtlirement for catalytic amounts of light for organotrophic growth. Light-grown y-2 cells given acetate are capable of the eqtuivalent of 9 to 10 divisions when placed in darkness. Cultulres adapt gradually to di,m white or monochromatic light and after 8 to 10 generations assume a steady state with respect to growth and pigment content.Two energeti,cally distinct li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The red LED condition was able to obtain the most characteristic differences because it was the best growth condition in this study. This growth trend corresponds with another study that found maximal chlorophyll content and cell volume in the red spectrum [ 30 ]. The result of this study suggests that red spectrum lighting is the most efficient evaluation condition because it gives rapid growth and characteristic growth rates.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The red LED condition was able to obtain the most characteristic differences because it was the best growth condition in this study. This growth trend corresponds with another study that found maximal chlorophyll content and cell volume in the red spectrum [ 30 ]. The result of this study suggests that red spectrum lighting is the most efficient evaluation condition because it gives rapid growth and characteristic growth rates.…”
Section: Resultssupporting
confidence: 91%
“…[ 29 ] applied 18–36 μmol m −2 s −1 of blue LED in a photo-bioreactor to produce astaxanthin using a Haematococcus pluvialis system suggesting that blue LED is a useful testing condition. However, the most efficient growth of C. reinhardtii had been observed around the red spectra in a study that employed a chlorophyll synthesis mutant [ 30 ]. The red spectrum mainly consists of 660 nm and is also an important wavelength for photosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…The studies presented above, documenting diversity at progressively smaller scales, could naturally be extended to assess the genetic variation that occurs within laboratory cultures of algae. Indeed, recognition that diversity can exist in cultures has come from identification and isolation of mutant individuals (Terborgh et al. 1967, Wollman 1979, Gieskes and Buma 1997).…”
mentioning
confidence: 99%